2009
DOI: 10.1021/ar800201v
|View full text |Cite
|
Sign up to set email alerts
|

Design of Selective Neuronal Nitric Oxide Synthase Inhibitors for the Prevention and Treatment of Neurodegenerative Diseases

Abstract: Nitric oxide (NO), which is produced from l-arginine by the nitric oxide synthase (NOS) family of enzymes, is an important second-messenger molecule that regulates several physiological functions. In endothelial cells, it relaxes smooth muscle, which decreases blood pressure. Macrophage cells produce NO as an immune defense system to destroy pathogens and microorganisms. In neuronal cells, NO controls the release of neurotransmitters and is involved in synaptogenesis, synaptic plasticity, memory function, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
128
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 56 publications
2
128
0
1
Order By: Relevance
“…The biological activities of NO are closely linked to the specific NOS isoform involved in its synthesis and deregulation of its biosynthesis leads to various pathologies (5). Data support the notion that inhibition of the inducible and neuronal isoforms iNOS and nNOS have therapeutic utility in the treatment of a variety of diseases, including septic shock, neurodegeneration, inflammation, and cancer (5,6). It was shown that the endothelial isoform eNOS participates in tumor initiation and maintenance, thus its inhibition could be beneficial in this context (7,8).…”
mentioning
confidence: 88%
“…The biological activities of NO are closely linked to the specific NOS isoform involved in its synthesis and deregulation of its biosynthesis leads to various pathologies (5). Data support the notion that inhibition of the inducible and neuronal isoforms iNOS and nNOS have therapeutic utility in the treatment of a variety of diseases, including septic shock, neurodegeneration, inflammation, and cancer (5,6). It was shown that the endothelial isoform eNOS participates in tumor initiation and maintenance, thus its inhibition could be beneficial in this context (7,8).…”
mentioning
confidence: 88%
“…Using this moiety, compound 22 ( Figure 7) and its optical isomer showed to be selective against nNOS, although unable to penetrate the blood-brain-barrier (BBB) in in vivo studies [15,47,48]. Trying to increase the CNS permeability, prodrug design approach was used in primary and secondary amines.…”
Section: N-substituted Acetamidinesmentioning
confidence: 99%
“…[7] The pronounced effect of NAMI-A on angiogenesis was confirmed in the chick allantoic membrane and in the rabbit eye cornea model. [8,9] It should be also noted that NO, which is produced by a number of nitric oxide synthase (NOS) enzymes from larginine in the body, [10] plays a major role as a signaling molecule in biological signal transducing systems, for example, in blood pressure regulation, [11,12] neurotransmission, [13,14] inflammatory response, [15,16] as well as necrosis [17] and apoptosis. [18,19] Nitric oxide is therefore essential in biological systems, but both its excess as well as deficiency leads to pathologies.…”
Section: Introductionmentioning
confidence: 99%